Konflik dan Resolusi Konflik Perkebunan (Studi Kasus Konflik Perkebunan Antara PT Perkebunan Nusantara V Sei Kencana Dengan Masyarakat Desa Senama Nenek Kecamatan Tapung Hulu Kabupaten Kampar) - Anugrah Dwi Putra; Eri Sayamar; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The land conflict is the problem that has been there since the colonial period and the problem solving about it seems very still slowly. The late of problem solving occurs in Senama Nenek village Sub-district of Tapung Hulu, Kampar District that consist of PT Perkebunan Nusantara V Sei Kencana group and the rural community of Senama Nenek and then in this conflict has been composed some strategies which will be used to achieve main goal. The strategy that will be analyzed by using QM For Windows to find which one the strategy that very suitable for both of group. The result of QM For Windows shows the maximin score and minimax are Rp.21. 000.000.000,-. Based on the result, the writer concluded that using Mediator Swasta Service was the best strategy. Keyword : Conflict, Plantation, Linear Programing